The Effects of International Financial Reporting Standards on Global Capital Markets - Sultan, Karam Hshim; Hassan, Hayder Mohammed; Mohamed, Jassim; Abbas, Nadia Ahmed; Kubiv, Stepan (Journal of Ecohumanism, 2024)
Background: The adoption of International Financial Reporting Standards (IFRS) has significantly reshaped financial reporting practices worldwide. As global capital markets increasingly rely on standardized financial information, understanding the implications of IFRS is crucial for investors, policymakers, and corporations. Objective: This study examines the effects of IFRS adoption on global capital markets, focusing on market efficiency, comparability of financial statements, and investment decision-making. Methods: Using a dataset of 1,200 publicly traded companies across 30 countries, the study employs a difference-in-differences approach to compare pre- and post-IFRS adoption periods. Key metrics analyzed include market liquidity, volatility, and cross-border investment flows. Results: The findings indicate that IFRS adoption leads to a 15% increase in market liquidity and a 10% reduction in stock price volatility. Additionally, the comparability of financial statements improved by 25%, facilitating a more robust investment environment. Cross-border investment flows increased by 20%, highlighting the positive impact on global capital mobility. Conclusion: The adoption of IFRS has markedly enhanced the efficiency and stability of global capital markets. By improving financial statement comparability and fostering investor confidence, IFRS contributes to a more integrated and dynamic international financial landscape. These results underscore the importance of continued global cooperation in financial reporting standards to support sustainable economic growth.IFRS